Efeitos metabólicos e inflamatórios da ingestão de glúten em mulheres saudáveis com sobrepeso e obesidade e sua associação com genótipo da haptoglobina - Rachel Bacha Silva (2019)
Aim: Several studies have shown the immunogenic role of gliadin, a wheat protein fraction. Effects of gluten intake on adiposity increase, thermogenesis reduction, changes in the gut microbiota, and intestinal permeability have already been documented in experimental models. In humans, some studies observed changes in dietary patterns; however, there is no clear evidence about the mechanisms of gluten effects in obesity. Therefore, our aim was to evaluate the effects of the controlled intake of wheat gluten (24g/day) on weight gain, body composition, dietary intake, metabolic rate and pro-inflammatory cytokines secretion in non-celiac women with overweight and obesity; and the association of these factors with the haptoglobin genotype. Methods: We designed a blind cross-sectional study. 42 pre-menopausal women, 18 to 50 years old, body mass index (BMI) from 24.9 to 35.4 kg/m², and no gluten-related chronic diseases were included. The volunteers were submitted to eight experimental weeks on a gluten-free diet. During this period, we recommended the maintenance of the usual diet and the intake of two muffins per day (gluten or gluten-free/placebo). The gluten-containing muffin and the gluten-free were identical but added with 12g of gluten. Data were collected at baseline (T0), at week four (T4), at the end of the experimental period (T8) and after five weeks with usual non-gluten-free diet (T13). We collected body weight, body composition by bioelectrical impedance analysis, basal metabolic rate (BMR) by indirect calorimetry, blood for cytokines analysis (IL6, TNF, and IL1β), and buccal cells (collected by swab) for haptoglobin genotyping. The haptoglobin encodes for two alleles Hp1 and Hp2. The allele Hp2 pre-haptoglobin, also known as zonulin, is a physiological regulator of tight junctions and it is released upon gluten stimulation. A 24-h dietary recall was collected weekly for evaluation of macronutrients intake and dietary inflammatory index (DII). Results: We observed a small reduction in body weight and BMI at the end of both interventions (gluten or placebo), which did not indicate any association with gluten intake or restriction. Analysis of the variation of each parameter (final minus initial) also showed no changes in the BMR or body composition after gluten or placebo. Related to the dietary pattern, only the protein intake (g/body weight) and percentage of fat were higher during gluten-muffin period, although not associated with the intervention. No difference in carbohydrate intake was observed. DII was lower in the post-study period (T13) when compared to T0-T8. Intriguingly, the presence of the Hp2 allele (higher zonulin producers) was negatively correlated to BMR/kg/lean mass and positively correlated to higher levels of IL6 and IL1β only during gluten-muffin period. Conclusion: We concluded that the gluten-free diet presented a higher DII when compared to the usual non-gluten-free diet. Significant changes in eating behaviour were not detected. Body weight, body composition, and BMR were not affected by the intake of gluten-muffin or placebo. The presence of Hp2 allele was associated with lower BMR and increased secretion of pro-inflammatory cytokines only during the gluten-muffin period. Any association was observed to placebo or the Hp1-1 genotype. Altogether, the data suggest that higher zonulin producers presented a worsen control of inflammation and lower metabolism upon gluten intake.